Eficiência hidrodinâmica de um decantador de fluxo ascendente modelado matematicamente com curvas braquistócronas - Morais, Fellipe José de (2019)
The use of environmental resources in a sustainable way has been a relevant topic in debates that deal with water waste. Improving efficiency in water treatment is one of the key factors when it comes to water suppliers, such as Sanepar. This improvement encompasses the hydrodynamic behavior of a decanter used to separate coarse solids in suspension in a mixture. The settling tank used by Sanepar is an upflow and constant washes are required to remove sedimentated solids, generating water expenses and affecting natural resources. Thus, the objective of this work was to propose a new geometry based on the brachistochrone for the settling tank, in order to evaluate its hydrodynamic behavior and its sedimentation and washing characteristics. For this, a modeling was sought by calculating the dimensions of the current model and, later, using brachistochrones curves in this model, in order to develop a new tank with the reduction of dead zones, causing a less wash periodicity and consequently a lower expense with water to be discarded. Maple® was used to obtain the representativeness of the project, besides studying the behavior of the tanks (current and proposed) by means of a computational fluid dynamics simulation applying the operational characteristics of Sanepar, verifying precisely and in detail their hydrodynamic performances. The results obtained evidenced a smaller amplitude of mass flow in the internal regions of the new model due to its greater behavioral range, with a value of 1.821 kg/s, while in the current model it is 2,701 kg/s. When analyzing other characteristics such as velocity, even with the approximate maximum velocity of both them being 0,09 m/s, it was observed a more extensive movement of the sludge in the lower part of the tank, reducing the preferred paths of displacement, besides to decrease the intensity of passage of this material with greater turbidity to the next stage of treatment, which in the current model reaches 0,021 m/s and in the proposed only 0,008 m/s. In this way, it was possible to conclude on the efficiency and viability of the obtained model based on these hydrodynamic data, allowing a comparison on a potential better use of water resources.